On the design of heat exchanger equipment for novel-type isobaric expansion engines. (25th February 2020) - Knoke, Torben; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny Y.
Highlights: A novel isobaric expansion engine (IEE) for heat-to-power conversion is proposed. A method to design and analyse heat exchanger equipment for IEE is presented. Attainability of up to 60% of the Carnot efficiency at heat source temperatures of 200 °C. Non-regenerative operation is beneficial in low-temperature applications. Abstract: The recently proposed idea of displacer-type heat engines with dense working fluids revived the long-known concept of isobaric expansion (IE). Capable of overcoming some of the most severe disadvantages of gas-phase displacer-type heat engines and state-of-the art ORC plants, these engines offer a solution for future heat-to-power conversion and heat driven pumps or compressors. Effective heat regeneration and heat transfer in general are key issues of all types of displacer-type heat engines and thus, compact heat exchangers with minimum internal volume and pressure drop are required. This study is dedicated to the effects of regeneration on efficiency and considers efficiency-abating internal (dead) volumes and pressure drop. Printed Circuit Heat Exchangers (PCHE) are proposed for application in IE engines and a design procedure for these apparatuses is introduced. The results show that efficiencies close to the optimum can be obtained if the channel size is below 1 mm. Along with recently presented theoretical and experimental studies on such IE engines, this affirms the great potential of this heat conversion technology.